The effectiveness of health education based on local wisdom of the people of Tulungagung Regency on maternal parenting in preventing stunting - Astuti, Dita Apriana Dwi; Winarti, Eko; Mirasa, Yudied Agung (BKM Public Health and Community Medicine, 2023)
Purpose: This study was to determine the effectiveness of Health Education Based on Local Wisdom of the People of Tulungagung Regency on Mother Parenting in Fulfilling Toddler Nutrition as an Effort to Prevent Stunting. Methods: This research uses a quasi-experimental approach. The research location is in Bandung District, Tulungagung Regency. The population is all mothers who have children under five (0-3 years) in Bandung District, Tulungagung Regency. The research sample consisted of 60 respondents which were divided into 30 treatment groups and 30 control groups, which were taken using cluster random sampling technique. Data was collected using a questionnaire that had been tested for validity and reliability before and after the education was implemented. Data analysis using a two-way ANOVA test. Results: There is an interaction of knowledge and parenting style variables together with time (pre-test and post-test) and group (intervention and control) when viewed from the p-value <0.05. The results of this analysis, the group of mothers who receive health education through the lecture method and local wisdom-based modules is related to the knowledge and parenting patterns of mothers. Conclusion: Health education interventions through the lecture method and local wisdom-based modules have been shown to have a significant effect on maternal parenting in stunting prevention.